2021
DOI: 10.14309/ctg.0000000000000324
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Reduces the Incidence of Hepatocellular Carcinoma in Patients With Chronic Hepatitis B Receiving Oral Nucleos(t)ide Analog

Abstract: INTRODUCTION: Aspirin may reduce the risk of chronic hepatitis B (CHB)-related hepatocellular carcinoma (HCC) in patients receiving antiviral treatment. We aimed to investigate the impact of aspirin on reducing HCC risk in patients treated with first-line oral nucleos(t)ide analogs (NAs; entecavir and/or tenofovir disoproxil fumarate). METHODS: We conducted a territorywide, retrospective cohort study in NA-treated CHB patients between 2000 and 2018 from the electronic h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…Nine studies (n = 115 124) reported on HCC incidence. [28][29][30][31][32][33][34][35][36] The pooled aHR from seven matched cohort and case-control studies…”
Section: Hcc Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies (n = 115 124) reported on HCC incidence. [28][29][30][31][32][33][34][35][36] The pooled aHR from seven matched cohort and case-control studies…”
Section: Hcc Incidencementioning
confidence: 99%
“…(n = 51 799) [28][29][30][31][32]35,36 which evaluated aspirin use compared to no aspirin use showed moderate evidence that aspirin is associated with a significantly reduced risk of HCC incidence; HR: 0.51, 95% CI: 0.36-0.72 (Figure 2A). The quality of evidence was downgraded one level for inconsistency.…”
Section: Hcc Incidencementioning
confidence: 99%
See 1 more Smart Citation
“…70 The most recent cohort study of 35,111 Hong Kong HBV patients receiving NA treatment reported consistent findings as well as dose-response relationship (HR: 0.65, 0.63 and 0.41 for 0.25-2, 2-5 and ≥ 5 years, respectively). 71 According to a cohort study based on Taiwan's National Health Insurance database, aspirin lowered HCC risk in HCV patients by about 50%. 72 A subsequent Taiwanese cohort study with a higher proportion of HCV-related cirrhotic patients reported consistent findings (HR = 0.78, 95% CI:0.64-0.95) but no statistical significance was observed in cirrhotic subgroup (HR = 0.75, 95% CI: 0.55-1.03).…”
Section: %) 68mentioning
confidence: 99%
“…Liver fibrosis refers to the pathological process of abnormal hyperplasia of connective tissue in the liver, which is an important factor affecting the prognosis of chronic liver disease. Clinical trials have found that patients with hepatitis B cirrhosis may show liver fibrosis and increased expression levels of serum inflammatory factors during treatment, leaving them in a microinflammatory state for a long time and thus affecting the therapeutic effect [ 5 ]. Entecavir, adefovir dipivoxil, and lamivudine, with antibacterial and antivirus effects, are common and effective clinical drugs to treat liver cirrhosis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%